An experimental study on the effect of cooperative learning on students' academic achievement and students' perceptions towards cooperative learning. (4th March 2017) - Parveen, Qaisara; Yousuf, M. Imran; Mustafa, Saima
ABSTRACT: The present study was anticipated to explore the impact of cooperative learning on students' speculative achievement at elementary level, inside the classroom environment. The principle target was to examine the scholarly accomplishment of an exploratory group with that of a control group. The control group was indicated using traditional strategies while the trial social event was instructed through cooperative learning. The framework of the study used a pre-test and post-test control amass, that is a type of a true experimental design. The students' academic achievement in the mathematics was the reliant variable and techniques for educating were the independent variables. The number of inhabitants in the study contained all the seventh grade understudies contemplating in the Government Girls High School, situated in Rawalpindi in Pakistan. The sample included 30 seventh grade understudies, selected randomly from the government school of Rawalpindi. The selected sample students were distributed into one control group and one experimental group on the basis of their pre-test scores. The information was broken down by applying a t-test at a .05 level of hugeness. It was induced that understudies taught through cooperative learning showed better results for their scholastic accomplishment on the post-test than those instructed through traditional techniques.